Fecal Microbiota Changes in Patients With Postpartum Depressive Disorder - Zhou, Yumei; Chen, Chen; Yu, Haibo; Yang, Zhuoxin (Frontiers in Cellular and Infection Microbiology, 2020)
Postpartum depressive disorder (PPD) is a unique subtype of major depressive disorder and a substantial contributor to maternal morbidity and mortality. However, the pathogenesis of PPD has still remained elusive, and it may associate with genetic and environmental factors. Gut microbiota has already been proved to be associated with depression; however, a limited number of studies have concentrated on PPD. The present study aimed to explore the potential correlations between gut microbiota and PPD. In this study, 57 participants were enrolled, in which fecal samples of 28 patients with PPD and 16 healthy controls (HCs) were collected and then analyzed by high-throughput sequencing of the 16S ribosomal RNA (rRNA) gene. The results showed that diversity and composition of gut microbial communities were partly different between PPD patients and HCs. The relative abundance of Firmicutes phyla was lower in PPD patients. The levels of several predominant genera were significantly different between PPD patients and HCs. More importantly, the PPD patients experienced reduced levels of Faecalibacterium, Phascolarctobacterium, Butyricicoccus, and Lachnospiraceae, as well as increased levels of Enterobacteriaceae family. In addition, a correlation was observed between levels of Phascolarctobacterium, Lachnospiraceae, Faecalibacterium, and Tyzzerella.3 and the severity of depressive symptoms. Various kinds of bacteria, such as Lachnospiraceae and Faecalibacterium, were found to be associated with levels of sex hormones. This study indicated the correlation between gut microbiota and PPD, and gut microbiota-based biomarkers may be helpful for the diagnosis and treatment of PPD patients. However, further studies need to be conducted to clarify the cause–effect relationship between PPD patients and gut microbiota and to highlight the suitability of gut microbiome as a biomarker.